Bridging Museum Mission to Visitors’ Experience: Activity, Meanings, Interactions, Technology - Recupero, Annamaria; Talamo, Alessandra; Triberti, Stefano; Modesti, Camilla (Frontiers in Psychology, 2019)
In recent years, the contribution of various disciplines and professionals (i.e. from marketing, computer science, psychology and pedagogy) to museum management has encouraged the development of a new conception of museology. Specifically, psychology has affected the overall conception of museum and the visitors towards a more holistic vision of the museum experience as a complexity of memory, personal drives, group identity, meaning-making process, as well as leisure preferences. In this regard, psychological research contributes to advance the scientific knowledge about psychological and social phenomena related to the visitor experience, as well as to design innovative technologies and future tourism services. The present contribution discusses the Socio-Cultural Activity Theory as a theoretical framework to conceptualize the museum visit as an activity mediated by the technology, and to better identify the factors shaping the interaction between the visitors and the technologies. To do so, a case study is presented: a qualitative research performed at the Ara Pacis Museum in Rome (Italy) to analyze the visitor experience of a tour that integrates augmented and virtual reality. Information derived from applying Activity Theory on visitors’ experience highlight the value of technology as mediating tool between the museum mission and the visitor experience, considering the interaction between visitors’ characteristics, museum environmental dimensions and technology’s features.